Predicting Hemolytic Uremic Syndrome and Renal Replacement Therapy in Shiga Toxin–producing Escherichia coli–infected Children. (24th May 2019) - McKee, Ryan S; Schnadower, David; Tarr, Phillip I; Xie, Jianling; Finkelstein, Yaron; Desai, Neil; Lane, Roni D; Bergmann, Kelly R; Kaplan, Ron L; Hariharan, Selena; Cruz, Andrea T; Cohen, Daniel M; et al.
Abstract: Background: Shiga toxin–producing Escherichia coli (STEC) infections are leading causes of pediatric acute renal failure. Identifying hemolytic uremic syndrome (HUS) risk factors is needed to guide care. Methods: We conducted a multicenter, historical cohort study to identify features associated with development of HUS (primary outcome) and need for renal replacement therapy (RRT) (secondary outcome) in STEC-infected children without HUS at initial presentation. Children aged <18 years who submitted STEC-positive specimens between January 2011 and December 2015 at a participating study institution were eligible. Results: Of 927 STEC-infected children, 41 (4.4%) had HUS at presentation; of the remaining 886, 126 (14.2%) developed HUS. Predictors (all shown as odds ratio [OR] with 95% confidence interval [CI]) of HUS included younger age (0.77 [.69–.85] per year), leukocyte count ≥13.0 × 10 3 /μL (2.54 [1.42–4.54]), higher hematocrit (1.83 [1.21–2.77] per 5% increase) and serum creatinine (10.82 [1.49–78.69] per 1 mg/dL increase), platelet count <250 × 10 3 /μL (1.92 [1.02–3.60]), lower serum sodium (1.12 [1.02–1.23 per 1 mmol/L decrease), and intravenous fluid administration initiated ≥4 days following diarrhea onset (2.50 [1.14–5.46]). A longer interval from diarrhea onset to index visit was associated with reduced HUS risk (OR, 0.70 [95% CI, .54–.90]). RRT predictors (all shown as OR [95% CI]) included female sex (2.27 [1.14–4.50]), younger age (0.83 [.74–.92] per year), lower serum sodium (1.15 [1.04–1.27] per mmol/L decrease), higher leukocyte count ≥13.0 × 10 3 /μL (2.35 [1.17–4.72]) and creatinine (7.75 [1.20–50.16] per 1 mg/dL increase) concentrations, and initial intravenous fluid administration ≥4 days following diarrhea onset (2.71 [1.18–6.21]). Conclusions: The complex nature of STEC infection renders predicting its course a challenge. Risk factors we identified highlight the importance of avoiding dehydration and performing close clinical and laboratory monitoring. Abstract : Among Shiga toxin–producing Escherichia coli –infected children without hemolytic uremic syndrome (HUS) brought for emergency department evaluation, 14% developed HUS. Younger age; elevated white blood cell count, hematocrit, and creatinine; early presentation; and delayed intravenous fluid administration predicted HUS.